Fabrication of hot-wire probes and electronics for constant temperature anemometers - Osorio, Orlando Darío (2010)
The purpose of this paper is to discuss the construction of constant temperature hot wire anemometers. Different options are analyzed for the fabrication of sensors and electronics. A practical and simple method is developed to manufacture the probe and associated electronics. The fabricated sensor has a diameter of 2 µm and approximately 500 µm in length. The associated electronics are designed to keep the sensor working at a constant temperature and allow the indirect measurement of speed. The design is simple, inexpensive and highly flexible regarding its use and modifications. The dynamic tests performed and the comparison with a commercial model shows a satisfactory performance. The unit built also includes an option for testing with a square wave, which is generated internally, and a comparator mode to measure the resistance of the sensor.